2014
DOI: 10.1111/jnc.12821
|View full text |Cite
|
Sign up to set email alerts
|

Tau‐targeting passive immunization modulates aspects of pathology in tau transgenic mice

Abstract: Immunization is increasingly recognized as a suitable therapeutic avenue for the treatment of neurological diseases such as Alzheimer's disease and other tauopathies. Tau is a key molecular player in these conditions and therefore represents an attractive target for passive immunization approaches. We performed such an approach in two independent tau transgenic mouse models of tauopathy, K369I tau transgenic K3 and P301L tau transgenic pR5 mice. The antibodies we used were either specific for full-length tau o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…These investigators evaluated three tau antibodies in the K369I (K3) transgenic tau mouse and in a P301L mouse model [71]. Antibodies with varying properties were selected for in vivo evaluation.…”
Section: Prothena Corporation Lars Ittner and Jürgen Götzmentioning
confidence: 99%
“…These investigators evaluated three tau antibodies in the K369I (K3) transgenic tau mouse and in a P301L mouse model [71]. Antibodies with varying properties were selected for in vivo evaluation.…”
Section: Prothena Corporation Lars Ittner and Jürgen Götzmentioning
confidence: 99%
“…Wood and Zinsmeister (1989) found that the anti-tau monoclonal antibodies Alz-50 and Tau-1 each blocked the binding of the other antibody to neurofibrillary tangles (NFTs) and neuritic plaques. Ittner et al (2015) similarly reported that administration of anti-pTau S404 antibody to transgenic tauopathy mice reduced the staining intensity of pS422 in hippocampal dental gyrus neurons. However, this result could have been due either to decreased phosphorylation of tau at S422 or to increased clearance of the pS422-reactive neurons.…”
Section: Discussionmentioning
confidence: 88%
“…In transgenic "tauopathy" mice which express human tau mutations, immunization with phosphorylated tau fragments (Asuni et al, 2007;Boimel et al, 2010) and administration of monoclonal antibodies specific for phosphorylated tau (Chai et al, 2011;Ittner et al, 2015) were found to reduce the development of tau pathology. Treatment with antibodies to non-phosphorylated tau also decreased brain levels of phosphorylated tau in tauopathy mice (Dai et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.) protein [26] and also serve as a valuable template for generating a pThr-peptide-focused human antibody library to bypass animal immunization [6].…”
Section: Resultsmentioning
confidence: 99%